Propofol sedation for colonoscopy with a new ultrathin or a standard endoscope: a prospective randomized controlled study - Töx, U.; Schumacher, B.; Toermer, T.; Terheggen, G.; Mertens, J.; Holzapfel, B.; Lehmacher, W.; Goeser, T.; Neuhaus, H. (Endoscopy, 2013)
Background and study aims: The majority of colonoscopies in Germany are performed under conscious sedation. Previous studies reported that pediatric colonoscopes reduce the demand for sedative drugs and may improve cecal intubation. The aim of this study was to compare a new ultrathin and a standard colonoscope in terms of propofol demand during colonoscopy.Patients and methods: A total of 203 patients were prospectively randomized to undergo colonoscopy with either a 9.5-mm ultrathin (UTC) colonoscope or a standard colonoscope of variable stiffness. Initially, 40 or 60 mg of propofol were administered according to body weight, followed by bolus injections of 20 mg as deemed necessary. Propofol was administered by a separate physician who was blinded to the endoscope used. Sedation levels were defined according to guidelines; pain and complaints were recorded on a numeric rating scale.Results: Significantly less propofol was required to reach the cecum with the UTC (adjusted mean 94.9 mg [95 % confidence interval (CI) 85.7 – 105.0] vs. 115.3 mg [95 %CI 105.8 – 124.7]; P = 0.003). The level of sedation and pain score were lower with the UTC (sedation level 1 76 % vs. 61 %; P = 0.003; pain score adjusted mean 2.0 [95 %CI 1.7 – 2.4] vs. 2.8 [95 %CI 2.5 – 3.1]; P = 0.001). The rate of ileal and cecal intubation, time to reach the cecum, number of external compressions, withdrawal time, polyp and adenoma detection rate, and patient satisfaction were not different between the two colonoscopes. The time to intubate the ileum was longer with the UTC (1.73 minutes [95 %CI 1.42 – 2.04] vs. 1.22 minutes [95 %CI 0.91 – 1.52]; P = 0.020). Conclusions: Use of a new ultrathin colonoscope was associated with reduced propofol consumption, lower patient sedation levels, and less pain than the standard colonoscope, but ileal intubation time was longer.